Stability Analysis and Reinforcement Treatment of Open Pit Slope. (May 2019) - Liu, Yunqiu; Wang, Xiaofei; Gao, Jiaxing
Abstract: The construction of mine surface facilities shall be carried out according to the scope of mining rights and ease of use. The underground mining of Shirengou Iron Mine uses filling method mining, and the filling station needs to be built on the surface. According to the design, it is constructed near the open pit. Based on the protection of the filling station system, the stability analysis of the open slope is needed. The failure mode of iron ore open slope is circular arc sliding failure mode. The calculation model of the stability analysis is calculated by the residual thrust method. The maximum residual thrust of the I-I section is 128.9 tons/meter, and the maximum residual thrust of the II-II section is 75.39 tons/meter. According to the calculation results, the safety measures such as slope dressing and masonry retaining wall are carried out on the open slope, and the grouting prestressed anchor cable is selected to reinforce the slope. The anchor cables are connected by reinforced concrete frame and beam, and the concrete is used. The beam acts as an anchor pier. In order to effectively consolidate the slope stability, the grouting method is combined to effectively treat the slope. After a series of slope reinforcement measures, the stability of the open slope and the safety of the filling station can be guaranteed.